2022
DOI: 10.3390/medicina58020319
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Involvement in Glioblastoma Treatment

Abstract: Glioblastoma multiforme (GBM) is one of the deadliest brain tumors. Current standard therapy includes tumor resection surgery followed by radiotherapy and chemotherapy. Due to the tumors invasive nature, recurrences are almost a certainty, giving the patients after diagnosis only a 12–15 months average survival time. Therefore, there is a dire need of finding new therapies that could potentially improve patient outcomes. Ferroptosis is a newly described form of cell death with several implications in cancer, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 135 publications
0
14
0
Order By: Relevance
“…GBM, formerly known as pleomorphic glioblastoma, also called glioblastoma, is the most common primary malignant brain tumor [ 1 ]. It is caused by malignant transformation of astrocytomas and is the most malignant type of astrocytoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…GBM, formerly known as pleomorphic glioblastoma, also called glioblastoma, is the most common primary malignant brain tumor [ 1 ]. It is caused by malignant transformation of astrocytomas and is the most malignant type of astrocytoma [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…ROS formation leads to lipid peroxidation (mainly phosphatidylethanolamine polyunsaturated fatty acids) that are destroying the lipid membranes, causing cell death. Ferroptosis is involved in several pathologies, including inflammatory pathologies, neurodegenerative diseases, cancers and I/R injuries (Liang et al, 2019;Capelletti et al, 2020;Reichert et al, 2020;Sun et al, 2020c;Mitre et al, 2022). In mice experimental models of I/R injury, ferroptosis inhibition reduces the intestinal ischemic area and also protects the lungs and liver against ischemia-induced remote injuries (Li et al, 2019bQiang et al, 2020;Deng et al, 2021).…”
Section: Ferroptosismentioning
confidence: 99%
“…GBM cells exhibit increased iron uptake and high free iron levels, implying their intrinsic predisposition to ferroptosis [ 10 , 11 ]. Moreover, recent studies have shown that in GBM promoting ferroptosis resulted in decreased tumor growth and treatment resistance [ 12 ]. These findings suggest that ferroptosis induction may be a potential modality, aiding the current post-operative treatments for GBM.…”
Section: Introductionmentioning
confidence: 99%